2007
DOI: 10.1088/0264-9381/25/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

The type N Karlhede bound is sharp

Abstract: We present a family of four-dimensional Lorentzian manifolds whose invariant classification requires the seventh covariant derivative of the curvature tensor. The spacetimes in questions are null radiation, type N solutions on an antide Sitter background. The large order of the bound is due to the fact that these spacetimes are properly CH 2 , i.e., curvature homogeneous of order 2 but non-homogeneous. This means that tetrad components of R, ∇R, ∇ (2) R are constant, and that essential coordinates first appear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…The relationship to curvature homogeneous spacetimes is addressed in [13]. Support for these conjectures in the 4D case is discussed in the next section.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The relationship to curvature homogeneous spacetimes is addressed in [13]. Support for these conjectures in the 4D case is discussed in the next section.…”
Section: Discussionmentioning
confidence: 92%
“…The relationship between CSI and curvature homogeneity in 4D is studied in [13]. In locally homogeneous spacetimes all of the sectional curvatures (Gaussian curvatures) are constant.…”
Section: D Csimentioning
confidence: 99%
“…In both cases the classes of solutions have been determined and shown to be parameterized by one function of one variable [12]. More recently, a study of four dimensional curvature homogeneous spacetimes has shown that CH 3 implies local homogeneity [15]; in addition, there exists a class of proper CH 2 spacetimes of Petrov type N, Plebanski-Petrov type N with a negative cosmological constant. The class of proper CH 2 spacetimes has been explicitly determined and shown to depend on one function of one variable [15].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we are interested in curvature homogeneity for a different, but related reason. As was shown in [18], curvature homogeneity is also a key concept in the search for maximal order metrics. The relevant observation is that for a CH k geometry the rank r k is small because t k = 0, and this is exactly what is needed for maximal order.…”
Section: Curvature Homogeneity and Pseudo-stabilizationmentioning
confidence: 92%